(untitled) - Davis, Kenneth C. (New York, 2001)
Don't know much about the Universe uses the now-familiar and popular question-and-answer format to inform and entertain listeners by examining a subject that has inspired the greatest of fascinations, produced many popular misconceptions,ultimately helped to shape the course of history.
Keywords: Astronomy,Thiên văn học,Cosmology,Vũ trụ học